Perubahan Sistem Perkawianan Masyarakat Besemah di Pagar Alam Provinsi Sumatera Selatan - Elta Dewi Nurhayati; Dadang Hikmah Purnama; Mery Yanti (Jurnal Empirika, 2016)
The title of this research is the Change of Marriage System at Besemah Society in Pagar Alam Province of south Sumatra. The problems investigated in this research were related to the causes of changes in the marriage system and the impact of changes towards the ancestry, the settle tradition after marriage, and the right to inheritance. This research aimed at understanding towards the changing in society marriage system. This research was a qualitative descriptive. In this research, purposive technique was used in order to determine the participants of the research: 13 participants were involved in this study which consisted of 2 traditional leaders, two people who expert about the tradition of Besemah, and 9 people who applied the same endean marriage system. The data were collected by using: in-depth interviews, observation, and documentation. Collected data is processed and analyzed. Taxonomy and triangulation techniques were used for analyzing data. The results of this study showed that there has been a change in society marriage system of Besemah from Kule berete to endean same, meanwhile the sources of change was reduced depend to their parents, job and the economy. The lineage society of Besemah was applied the marriage system same endean was patrilineal, and settle tradition after marriage is patrilocal, and the right to inheritance is based on the Islamic Sharia, an inheritance was a collective property, a son who becomes heir, all biological children as a heir but son got inherit more than girl, the distribution of the inheritance when the heir passed away.